Specialisation in pollen collection, pollination interactions and phenotypic variation of the oil-collecting bee Chalepogenus cocuccii - Maubecin, Constanza Clara (2020)
Bee pollen gathering from a few related plant species is a specialisation known as oligolecty. Although it is an extended phenomenon, it has been scarcely explored in oil-collecting bees. At the geographic level, there is little information about oligolecty persistence and also about phenotypic variation of bees related with abiotic factors. We studied the pollen collection specialisation of the oil-collecting bee Chalepogenus cocuccii, its pollination interactions and phenotypic variation across its distribution range, by analyses of pollen loads, field observations and morphometric measurements. Observations and pollen analyses showed that across its distribution range, C. cocuccii preferred Nierembergia flowers not only for oil but also for pollen. We found two bee-morphotypes, though phenotypic variation was not related to abiotic variables. We postulate that C. cocuccii is a narrowly oligolectic species, phenotypically and ecologically specialised in Nierembergia.